Between Representation and Construct of Childhood - Żynis, Bernadetta (Porównania, 2023)
The article refers to the book Representations and Constructs of Childhood in the Literature and Culture of the 20th and 21st Centuries, edited by Alicja Dąbrowska, Robert Mielhorski and Beata Morzyńska-Wrzosek, Wydawnictwo Uniwersytetu Kazimierza Wielkiego, Bydgoszcz 2022. This is a collective monograph devoted to the presentation of the image/figure of the child in fictional and intimate literature, literature for adults and for children, as well as in textbooks, theatre, photography, congratulatory cards, and painting. The way the child is portrayed in the art space is changing. Contemporary portrayals of the child fluctuate between representation and construction of his or her image, but the conviction of the creators and the awareness of the audience that any presentation is closer to creation than to “mimetic representation” seems to prevail. The authors present a wide range of approaches, which makes the book under review an interesting read.